STUDY ON PATHOGENICITY OF PASTEURELLA MULTOCIDA WHICH ISOLATED FROM FARM ANIMALS AND MAN - Mobarak, S. S. A.; Shubber, A. K.; Raheem, A. S. (The Iraqi Journal of Veterinary Medicine, 2021)
This study was described for the nature of the pathpgenesis of bacteria Pasteurella multocida which was isolated from infected man made comparison between these bacteria and those from infected farm animals. The percentage of Pasteurella multcida diagnosed bacteria from animals and human was 29.4% and 16.9% respectively. Comparing to other culture media Pasteurella multocida selective agar medium was characterized by its selectivity and sensitivity and then was attempt for biotyping species and subspecies of isolated Pasteurella from animals and human samples were successfully achieved. Pathogenicity test was performed on mice, only nine human isolatetes and twenty-one animal isolates from Pasteurella multocida were virulent. Todistinguish between the pathogenesis of human and animal isolates, one isolated from human and animal were chosed, in addition to the standared strain. The mice had been experimentally infected by three different ways, I/P, I/T, I/Eye. The results were showed that Pasteurella multocida can produce lesions as fibrinous suppurative pneumonia in lungs, liver and spleen which were detected histopatho logically. However the animal isolates were more virulent than human or standared strain.